A general and practical route to 4, 5-disubstituted oxazoles using acid chlorides and isocyanides1. Issue 65 (16th July 2015) - Tiwari, Dipak Kumar; Pogula, Jaya; Tiwari, Dharmendra Kumar
<x xml:space="preserve">Abstract</x> An efficient and mild method for the synthesis of 4, 5-di-substituted oxazoles via [3 + 2] cycloaddition reaction of isocyanides and acid chlorides is reported.